Let's break down the problem step by step.
-
Understanding the Current Ages:
- Let \( a \) be Tony’s current age.
- Since Andrea is 6 years younger than Tony, her current age can be expressed as \( a - 6 \).
-
Ages in Two Years:
- In two years, Tony’s age will be \( a + 2 \).
- In two years, Andrea’s age will be \( (a - 6) + 2 = a - 4 \).
-
Setting Up the Equation: According to the problem, in two years, Tony's age will be three times Andrea's age. This can be formulated as: \[ a + 2 = 3(a - 4) \]
Now, let's identify which of the given equations can be used to find Andrea's and Tony's current ages.
- Checking the options:
-
\( a + 2 = 3(a - 6 + 2) \)
- This simplifies to \( a + 2 = 3(a - 4) \), which is our equation. (Correct)
-
\( a = 3(a + 2) \)
- This does not align with our problem statement. (Incorrect)
-
\( 3(a + 2) = a - 6 + 2 \)
- This simplifies to \( 3(a + 2) = a - 4 \), which is not correct. (Incorrect)
-
\( a + 2 = 3(a + 6 + 2) \)
- This simplifies to \( a + 2 = 3(a + 8) \), which is not correct. (Incorrect)
-
Thus, the correct equation to find Andrea's and Tony's current ages is:
\( a + 2 = 3(a - 4) \), which is represented by option 1:
\( a + 2 = 3(a - 6 + 2) \).